Jonah and the worm - Briscoe, Jill. (Nashville : T. Nelson Publishers, 1983)
A retelling of the Old Testament story of Jonah using worms as the principal characters. Each chapter is followed by discussion questions and suggestions of prayers.
Keywords: Christian life -- Juvenile literature; Children -- Religious life; Bible stories, English -- O.T. Jonah; Christian life